Effect of Buspirone on the Behavioral Regulation of Rats in Low versus High Anxiety Conditions - Lim, Lee Wei; Temel, Yasin; Visser-Vandewalle, Veerle; Steinbusch, Harry; Schruers, Koen; Hameleers, Rob; Esquivel, Gabriel; Griez, Eric; Blokland, Arjan (Arzneimittelforschung, 2008)
Buspirone (CAS 33386-08-2) is reported to have anxiolytic effects in humans and is mostly described for mild anxiety. To further explore the effects of buspirone on different levels of anxiety, the effect of buspirone was evaluated in two different conditions of the open field which were distinguished as low and high anxiety (enclosed and exposed open field, respectively).Twenty-eight albino Wistar rats (350–400 g) were tested in two different arena settings, an enclosed and an exposed open field. Fourteen animals were initially injected with 1 ml saline while the others (n = 14) received buspirone 3 mg/kg.The data showed clear differences in the two open-field settings, suggesting a higher anxiety level in the exposed open field. In addition, correlation analysis showed that the two anxiety tests measure different aspects of anxiety. Buspirone treatment reduced the behavioral activity in both the enclosed and exposed open field, which is generally interpreted as an anxiogenic effect. However, buspirone increased the time in the center areas and decreased the frequencies in the outer regions. These behavioral changes are generally seen as an anxiolytic effect. Correlation analysis showed that buspirone treatment disrupted the relation between indices of anxiety.These results showed that in an open-field setting buspirone appears to have a dual effect. The reduced activity and increase in time spent in the center areas are indicative of both an anxiogenic and an anxiolytic effect, respectively. This was found in both open-field settings, suggesting that the effects of buspirone are independent of the anxiety level.
Keywords: Anxiolytics; Buspirone, anxiety conditions, rat; CAS 33386-08-2